RNA preservation in human dental pulp for transcriptomic profiling: a comparative multi-parameter study - Bhat, Raksha; Shetty, Preethesh; Shetty, Shishir (Frontiers in Dental Medicine, 2025)
ObjectivesDental pulp tissue presents unique challenges for RNA analysis due to its fibrous nature, elevated RNase expression, and susceptibility to degradation during extraction procedures. This study systematically evaluated three distinct preservation methodologies to determine optimal approaches for maintaining RNA integrity and quality in human dental pulp tissue.MethodsDental pulp samples were obtained from thirty-six patients diagnosed with irreversible pulpitis requiring endodontic treatment. Tissues were preserved using three methods: snap freezing in liquid nitrogen, RNAiso Plus reagent preservation, and RNAlater solution storage. RNA quality was comprehensively assessed using multiple complementary approaches; Nanodrop spectrophotometry, Qubit fluorometry, and Bioanalyzer capillary electrophoresis. Parameters assessed were yield quantification, purity assessment and structural integrity.ResultsRNAlater storage demonstrated statistically significant superior performance across all evaluated parameters. Yield analysis showed an 11.5-fold enhancement relative to snap freezing (4,425.92 ± 2,299.78 vs. 384.25 ± 160.82 ng/μl, p < 0.001) and 1.8-fold improvement over RNAiso Plus extraction. Integrity assessment indicated significant advantages with RNAlater samples exhibiting mean RIN values of 6.0 ± 2.07 compared to snap freezing at 3.34 ± 2.87 (p = 0.028). Quality evaluation demonstrated RNAlater samples achieved optimal RNA quality in 75% of cases while snap freezing achieved this standard in only 33% of samples.ConclusionRNAlater storage establishes as the optimal preservation approach for dental pulp RNA investigations, delivering enhanced yield, purity, and integrity parameters. The results furnish credible affirmation for establishing methodological standardisation in dental transcriptomics investigations and clinical implementations.